2020
DOI: 10.1111/jdv.16135
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and satisfaction of surgical treatment for hidradenitis suppurativa

Abstract: Background Surgery is a radical treatment for hidradenitis suppurativa (HS) and may be considered as the only one potentially curative. Objectives To characterize HS recurrence in patients after surgery and assess the risk factors of recurrence. Methods We conducted a monocentric retrospective cohort study. All consecutive patients who had surgery (January 1, 2012 to March 31, 2017) were included. We estimated the rate of recurrence of HS lesions after surgery (<1 cm from the scar), and recurrence‐associated f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
43
1
10

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(60 citation statements)
references
References 22 publications
6
43
1
10
Order By: Relevance
“…A study by Ovadja et al 2 in The Netherlands, of 107 surgical interventions for HS for 54 patients, found a 32% recurrence rate after a median 30month follow-up period. The 8 week healing time of the current study is also comparable to the 6 weeks that Ovadja et al 2 reported and the 3.3 months reported by Fertitta et al 1 A systematic review by Bouazzi et al 3 found that, of 54 relevant articles on post-operative HS complications and recurrences, there was an overall mean complication rate of 24% and a mean recurrence rate of 20%. Due to the high rates of post-surgical recurrence for HS in the literature, a retrospective review of surgical treatment of HS 4 concluded that recurrence of HS should be viewed as a feature of the Figure 2 Recurrence rates following first, second and third surgery.…”
Section: Hidradenitis Suppurativa: a Review Of Post-operative Outcomessupporting
confidence: 86%
See 1 more Smart Citation
“…A study by Ovadja et al 2 in The Netherlands, of 107 surgical interventions for HS for 54 patients, found a 32% recurrence rate after a median 30month follow-up period. The 8 week healing time of the current study is also comparable to the 6 weeks that Ovadja et al 2 reported and the 3.3 months reported by Fertitta et al 1 A systematic review by Bouazzi et al 3 found that, of 54 relevant articles on post-operative HS complications and recurrences, there was an overall mean complication rate of 24% and a mean recurrence rate of 20%. Due to the high rates of post-surgical recurrence for HS in the literature, a retrospective review of surgical treatment of HS 4 concluded that recurrence of HS should be viewed as a feature of the Figure 2 Recurrence rates following first, second and third surgery.…”
Section: Hidradenitis Suppurativa: a Review Of Post-operative Outcomessupporting
confidence: 86%
“…Despite the current recurrence rate seeming high at 30% after the initial surgery and 25% after the second surgery, these results are in keeping with similar studies from other countries. A retrospective cohort study in France by Fertitta et al 1 , of 75 patients, found a recurrence rate of 35% across a total of 115 surgeries for HS. A study by Ovadja et al 2 in The Netherlands, of 107 surgical interventions for HS for 54 patients, found a 32% recurrence rate after a median 30month follow-up period.…”
Section: Hidradenitis Suppurativa: a Review Of Post-operative Outcomesmentioning
confidence: 99%
“…The top three reported complications were infection (n = 13), postoperative bleeding (n = 10), and dehiscence (n = 7), and other reported complications included pain and contracture/stricture of scar, delayed wound healing, hypergranulation, decreased mobility, and hypertrophic scar. Three studies reported the complication rate by lesion number, with a 26.1% complication rate across lesions (96 of 367 lesions had a complication; 4 lesions were excluded from the complication analysis by one author [21]). The top three complications among these three studies included wound dehiscence (n = 58 lesions), infection (n = 8 lesions), and contracture (n = 7 lesions), and other reported complications included lymphedema and scar retraction.…”
Section: Excision: Complicationsmentioning
confidence: 99%
“…Moreover, ultrasound can help in evaluating and differentiating the various types of fistulas and choosing whether to use surgery or medical therapy. 6 Fertitta et al 1 have retrospectively measured the satisfaction of patients undergoing surgery for hidradenitis: US will be fundamental in evaluating the degree of satisfaction of patients undergoing medical or surgical therapy in a proseptic way. A better staging obtained through ultrasound can, in fact, allow to achieve a better degree of satisfaction and also guarantee lower recurrence rates.…”
mentioning
confidence: 99%
“…Skin and soft-tissue infections associated with Aeromonas species in French Guiana: an 11-year retrospective study Editor Aeromonas species are Gram-negative bacilli, commonly found in salted and fresh water, food and soil. 1 Skin and soft-tissue infections (SSTIs) are frequent 2 and have been reported in Australia, 1 Asia 3 and the Indian Ocean. 4 However, data from South America are scarce.…”
mentioning
confidence: 99%